6) a)- 12 × [-17 + 15 × (+ 59 – 27 – 30) – 21] =
b) + 29 × [-73 +21 × (-47 + 11 + 32) + 155] =
c)-31 × [+65-37×(-61 +26 + 36) -31] =
Răspunsuri la întrebare
Răspuns de
3
Răspuns:
Explicație pas cu pas:
a)-12×[-17+15×(+59-27-30)-21]=
-12×[-17+15×(32-30)-21]=
-12×[-17+15×2-21]=
-12×[-17+30-21]=
-12×[-13-21]=
-12×(-28)=408
b)+29×[-73+21×(-47+11+32)+155]
+29×[-73+21×(-36+32)+155]=
+29×[-73+21×(-4)+155]=
+29×[-73+(-84)+155]=
+29×[-157+155]=
+29×(-2)=-58
c) -31×[+65-37×(-61+26+36)-31]=
-31×[+65-37×(-35+36)-31]=
-31×[+65-37×1-31]=
-31×[+65-37-31]=
-31×[+28-31]=
-31×(-3)=93
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă